Estoque de biomassa e carbono na região noroeste do estado do Rio Grande do Sul, Brasil - Erthal, Daniele Arndt (2017)
The remnants of vegetation native to the Atlantic Forest account for about 22% of their original cover and are in different stages of regeneration. The typologies belonging to the biome and found in the northwest of the state of Rio Grande do Sul are mixed ombrophilous forest and deciduous seasonal forest. Amid the consequences of the current dynamics of land use and occupation caused by man, there is the fragmentation of primary and secondary forests, where an area continues to result in a large number of isolated fragments of different sizes. Among the various environmental services provided by forest ecosystems, the most important is the sequestration and storage of carbon in the form of biomass. Thus, the role of native forests in the removal and stocking of carbon is fundamental, demonstrating the need to develop new methods that estimate forest biomass and carbon by non-destructive methods. The objective of the present work is to estimate and study the dynamics of biomass and forest carbon stock in successional stages of regeneration in the Northwest Region of the State of Rio Grande do Sul. The study area is located in the Northwest of the State of Rio Grande do Sul , Covering two microregions, Três Passos and Frederico Westphalen. For this study two methodologies were developed to estimate the forest biomass stock, both based on remote sensing data. The study in the first methodology was carried out for the dates of 1985, 1994, 2005 and 2014, and covers an area of 9,046.9 km². The classification of forest successions in regeneration stages was a continuation of the work of Rosa (2016), where the size classes: initial (<5 ha), medium (5 - 10 ha), advanced (> 10 ha), later Biomass for them. For the second methodology, images from each year were used from 1985 to 2014, where the NDVI was calculated, and through regression generated for the global model, to obtain the IAF and to estimate the forest biomass. Subsequently, comparing both methodologies were compared among themselves, and compared with values provided by the methodology of the Brazilian Forest Service. For the first study, forest biomass in 2014 in the Northwest Region of the state of Rio Grande do Sul was 80,831 Gg, divided into three stages of initial (659 Gg) regeneration (2,549 Gg) and advanced (77,623 Gg) regeneration. In the study area, there are three protected areas, the Turvo State Park, the Nonoai Indigenous Reserve and the Guarita Indian Reserve, which account for almost 25% of the total stock of the region, and are significant areas in the carbon stock. The carbon estimated by the first methodology was 296 Gg for the initial stage, 1,147 for the medium stage and 34,930 for the advanced stage, totaling 36,373 Gg. For the second methodology, it was possible to observe the great relation between the increase of the LAI as a function of NDVI and the forest biomass in 2014 was 61,156 Gg, where 602 Gg corresponds to the initial regeneration stage, 8,287 Gg for the medium stage and 52,267 Gg for The advanced stage of regeneration. The estimated total carbon for the study area in 2014 according to the second methodology was 27,520 Gg CO2, of which 271 Gg were present in the initial stage, 3,729 Gg in the medium stage and 23,520 Gg in the advanced stage of regeneration. In the comparison of the methodologies developed in this study, a difference of 19,675 Gg was obtained, due mainly to the effects of edges of the studied fragments. Comparing the first and second methodologies developed with that provided by the Brazilian Forest Service, only 10 and 14.30% of the estimated values for forest biomass were obtained.